2009
DOI: 10.1186/1754-1611-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Solving a Hamiltonian Path Problem with a bacterial computer

Abstract: Background: The Hamiltonian Path Problem asks whether there is a route in a directed graph from a beginning node to an ending node, visiting each node exactly once. The Hamiltonian Path Problem is NP complete, achieving surprising computational complexity with modest increases in size. This challenge has inspired researchers to broaden the definition of a computer. DNA computers have been developed that solve NP complete problems. Bacterial computers can be programmed by constructing genetic circuits to execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…Synthetic systems have demonstrated the feasibility of flipping multiple overlapping regions flanked by a series of hix sites (Ham et al 2008;Haynes et al 2008;Baumgardner et al 2009). The flipping reaction appears to operate efficiently over inter-hix distances ranging from 100 bases to 5 kb (Ham et al 2008 and references therein), and the enhancer sequence can function several kilobases from these sites (Moskowitz et al 1991).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic systems have demonstrated the feasibility of flipping multiple overlapping regions flanked by a series of hix sites (Ham et al 2008;Haynes et al 2008;Baumgardner et al 2009). The flipping reaction appears to operate efficiently over inter-hix distances ranging from 100 bases to 5 kb (Ham et al 2008 and references therein), and the enhancer sequence can function several kilobases from these sites (Moskowitz et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The proteins Q and R might be enzymes in a double auxotroph strain; alternatively, they might confer resistance when cells are grown in a medium containing two different antibiotics. Finally, it has been shown that a hixC site can be inserted in the coding region of the green fluorescent protein (GFP) gene, allowing it to be reversibly ''split'' by DNA inversion events (Baumgardner et al 2009). The utility of this unusual property will become clear as our discussion proceeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several small scale systems have been constructed, either in the lab or in simulation (Amos 2004). Other examples of in vitro implementations of cellular computing systems include band detectors, coupled oscillations (Basu et al 2004(Basu et al , 2005 and, more recently, a solution to the three vertices Hamiltonian path problem (Baumgardner et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Bacterial computers provide a unique alternative technology to silicon computers. Cellular computers have the advantage of exhibiting enormous parallel computing capabilities, intercellular communication, ability to interface with the biological world, and reusability 5,6 . Computing efficiency may result from the use of single analog logic gates in a population of bacterial computers, as opposed to the thousands of gates required in digital processes used by conventional computers 7 .…”
Section: Introductionmentioning
confidence: 99%